REKONTRUKSI PRINSIP RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA ANAK - Aksar; Umar Dinata; Saut Maruli Tua Manik (JOURNAL EQUITABLE, 2023)
Restorative Justice according to Article 1 number 6 of Law Number 11 of 2012 is the settlement of criminal cases involving perpetrators, victims, families of perpetrators/victims, and other related parties to jointly seek a fair settlement by emphasizing recovery. return to its original state, and not retaliation. The concept of restorative justice is a critique of the concept of the criminal justice system which sees crime as a violation of state rules. As for the results of this study, namely the reconstruction of restorative justice policies in cases of children as perpetrators of crimes, according to Erna Sofwan Syukri, it provides an understanding of punishment as an effort to awaken the perpetrators of crimes so that they regret their actions, and return them to become good, law-abiding citizens. upholding moral, social and religious values, so as to achieve a safe, orderly and peaceful society. So the reconstruction of Restorative Justice in the case of children as perpetrators of criminal acts must be fair. The value of justice is a balance between rights and obligations and receiving rights and carrying out obligations.